DESIGN AND BUILD OF AUTOMATIC WASTAFEL USING ULTRASOUND HC-SR04 SENSOR BASED ON ARDUINO - Prasetyo, Henry Prasetyo; Rofi’i, Mohammad; Kurniasari, Septiana; Pamungkas, Muhammad Wisnu (Department of Physics, Maulana Malik Ibrahim State Islamic University of Malang, 2021)
The lack of public concern for washing hands during the Covid-19 pandemic, the authors designed an automatic sink using an arduino-based HC-SR04 ultrasound sensor to attract the public's interest. By making automatic sink technology using the HC-SR04 ultrasound sensor based on Arduino for use in hand washing by the community. This study uses experimental research that examines the effect of automatic washbasin with people's behavior in washing hands. By testing the use of water in 20 seconds, 43 people can use it in one day, and soap can be used by 6 people in one day in 5 seconds. The automatic sink using the HC-SR04 ultrasound sensor based arduino can be used with a distance that is made less than 15cm designed to be practical and sterile because it is used that does not touch faucets or soap. The conclusion of the study is that if there is an object that approaches the ultrasound sensor within a distance of less than 15cm, the water pump will be active for 20 seconds or the soap pump for 5 seconds will automatically come out. And it will run out if used for 934 seconds in 1 liter gallon or 46 people a day and the use of soap for 5 seconds will run out approximately 6 people in one day.